POJOK SIKAT GIGI: WORKSHOP FOR TEACHERS AT KB-TK SEPULUH NOVEMBER SURABAYA FOR THE DEVELOPMENT OF CO-CURRICULAR DENTAL HEALTH PLANS - Maharani, Aulia Dwi; Lestari, Gunarti Dwi; Paramita, Ayulistya (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community service program was carried out at KB-TK Sepuluh November Surabaya with the aim of improving teachers’ capacity in developing co-curricular learning plans related to dental health for early childhood students. Initial observations and dental examinations showed that the prevalence of dental caries among students was still high, and previous oral health education activities were not performed routinely. Therefore, a workshop was conducted to strengthen teachers’ knowledge and skills regarding dental health education and the creation of structured, interactive co-curricular learning plans. The workshop consisted of theoretical material on early childhood learning approaches and practical demonstrations on proper toothbrushing techniques. Teachers then developed co-curricular lesson plans and practiced guiding students in group toothbrushing activities. The results showed that teachers demonstrated increased understanding and were able to produce applicable learning plans and implement them confidently. This program is expected to support the sustainability of dental health education in schools and contribute to improving children’s dental hygiene behaviors.